NOVEL KARTINI KISAH YANG TERSEMBUNYI KAYA AGUK IRAWAN MN ANALISIS FEMINISME LIBERAL - Andriani Sandi Fransiska; Luluk Isani Kulup (Buana Bastra, 2018)
"Novel Kartini" The Hidden Story is the work of Aguk Irawan MN.Novel which describes the life of a woman who demands her right to be equal with men. Kartini's character is an independent female figure who wants to gain the struggle to get education, liberate women from injustice or discrimination to obtain education, and indigenous discrimination that gives rise to injustice for women. Kartini is a Javanese woman born of a common woman. But Kartini has a high spirit spirit in order to get a good education for himself and his people. Kartini also has the spirit to become teachers, doctors, and midwives in order to educate their people and help deliver the mother who gave birth to her baby could be saved. But, Kartini's fate is so bad. Until Kartini 25 years old Kartini married degan man who is paired by his father with his royal friend and at that age also Kartini has died. Kartini at that time also known as pioneer of indigenous revival which with spirit high writing letters to his best friend that he wanted to rebel so that women's lives can be synchronized with men in general.